Suitability of Indian Finger Millet for Malting: A Pilot Study: Finger millet as a gluten-free malt source - Kumar, Dinesh; Dr Salej Sood; Dr. Lakshmi Kant (Journal of Cereal Research, 2025)
Forty-six finger millet genotypes including 23 released varieties grown across the country were evaluated for grain and malt quality traits for two consecutive years to identify suitable genotypes for quality malt extraction. The grain protein content of genotypes varied from 5.6-10.6 in first year and 6.1-12.0 in the second year. All the finger millet genotypes showed high malt yield in both the years of evaluation. Best genotype for Hot Water Extract (HWE) was VL 348 (61.3%) in first year and IE 518 (60.5%), VHC 3766 (60.3%), VL 352 (64.1%), VL 384 (66.0%) were in second year. Overall, the results indicated that although variability is present in finger millet genotypes for malt quality traits, it may need separate breeding programme to select genotypes for malt with superior malting quality. Keywords: Eleusine coracana, Finger Millet, Hot water extract, Malt yield, Protein content